Establishment of Land Rights on Lar Land in Critical Forest Areas as a Strategy for Sustainable Forest Management - Dianto, Dianto; Gunawan, Jasardi (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
Land criticism in forest areas is a significant issue faced by many countries. This study analyzes the development of Lar land rights as a strategy for sustainable forest management in Sumbawa. Through empirical methods, the study shows that the integration of Lar with communal grazing and livestock can increase economic, ecological, and social growth. From a regulatory perspective, the implementation of Lar is supported by regional regulations and decisions of the Regent and Minister regarding forest areas. The study results indicate that the Lar scheme effectively deals with critical land while supporting sustainable forest management. As a next step, it is recommended that a more in-depth study be conducted on the long-term effectiveness of the Lar scheme, including its impacts on ecosystem sustainability and the active involvement of local communities in forest management